Increased forest carbon storage with increased atmospheric CO2 despite nitrogen limitation: a game‐theoretic allocation model for trees in competition for nitrogen and light. (18th December 2014) - Dybzinski, Ray; Farrior, Caroline E.; Pacala, Stephen W.
Abstract Changes in resource availability often cause competitively driven changes in tree allocation to foliage, wood, and fine roots, either via plastic changes within individuals or through turnover of individuals with differing strategies. Here, we investigate how optimally competitive tree allocation should change in response to elevated atmospheric CO2 along a gradient of nitrogen and light availability, together with how those changes should affect carbon storage in living biomass. We present a physiologically‐based forest model that includes the primary functions of wood and nitrogen. From a tree's perspective, wood is an offensive and defensive weapon used against neighbors in competition for light. From a biogeochemical perspective, wood is the primary living reservoir of stored carbon. Nitrogen constitutes a tree's photosynthetic machinery and the support systems for that machinery, and its limited availability thus reduces a tree's ability to fix carbon. This model has been previously successful in predicting allocation to foliage, wood, and fine roots along natural productivity gradients. Using game theory, we solve the model for competitively optimal foliage, wood, and fine root allocation strategies for trees in competition for nitrogen and light as a function of CO2 and nitrogen mineralization rate. Instead of down‐regulating under nitrogen limitation, carbon storage under elevated CO2 relative to carbon storage at ambient CO2 is approximately independent of the nitrogen mineralization rate. This surprising prediction is a consequence of both increased competition for nitrogen driving increased fine root biomass and increased competition for light driving increased allocation to wood under elevated CO2.